The interleukin-1 receptor/Toll-like receptor superfamily: signal generators for pro-inflammatory interleukins and microbial products - O'NEILL, LUKE; BOWIE, ANDREW (My University, 2000)
The interleukin-1 (IL-1) receptor/Toll-like receptor (TLR) superfamily is a recently defined and expanding group of receptors that participate in host responses to injury and infection. The superfamily is defined by the Toll/IL-1 receptor (TIR) domain, which occurs in the cytosolic region of family members, and is further subdivided into two groups based on homology to either the Type I IL-1 receptor or Drosophila Toll receptor extracellular domain. The former group includes the receptor for the important Th1 cytokine IL-18, and T1/ST2, which may have a role in Th2 cell function. The latter group includes six mammalian TLRs, including TLR2 and TLR4, that largely mediate the host response to gram-positive and gram-negative bacteria, respectively. Whether bacterial products are actual ligands for TLRs, or whether they generate ligands via as yet unidentified pattern recognition receptors, has yet to be determined. Signaling pathways activated via the TIR domain trigger the activation of downstream kinases, and transcription factors such as NF-kappaB, and involve the adaptor protein MyD88, which itself contains a TIR domain.
PUBLISHED
PMID: 10770283
Keywords: Biochemistry; Immunology, Inflammation & Infection; Neuroscience